Pengaruh Pandemi Covid-19 terhadap Fluktuasi Harga Saham dan Volume Transaksi Saham Supermarket di BEI - Sari, Imelda (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2023)
This study aims to determine the decline or increase in stock prices and stock transaction volume after the announcement of the arrival of Covid-19 in Indonesia. The companies studied were companies belonging to the D113 supermarket sector, consisting of AMRT, HERO, MIDI, MPPA, AND RANC. The research time is 35 days of stock transactions before March 2 2020 and 35 days of stock transactions after March 2 2020. The research approach uses quantitative analysis. This study uses secondary data, namely stock price data and stock transaction volume data. The analytical method used is multiple linear regression using SPSS, namely the Normality Test followed by the T-Test Paired Samples Test. The results of the study found that stock prices and stock transaction volume had different results. Share prices have decreased after the entry of Covid-19, but the volume of stock transactions has actually increased. Supermarket management to take steps to adjust quickly and accurately to changes that occur as a result of the government's mobility restrictions. It is hoped that the stability of sales in supermarkets will be able to increase sales so that investors want to buy shares, so that share prices rise again. Keywords: Stock Price, Stock Volume, Supermarket